The Role of Safety Leadership in Shaping Safety Culture: The Mediating Role of Communication and Commitment - Farhan , Akmal; Ambarwati, Rita; Dedy (Jurnal Manajemen Bisnis, 2025)
This study aims to link safety leadership to safety culture and safety climate as intermediaries. The research method used is a survey. Statistical analysis used to test the hypothesis with SEM-PLS, a sample of 317 was taken with a saturated sampling technique and used second-order data processing. The results of the study indicate a positive correlation between safety leadership and safety culture and safety climate. The conclusion of this study is that safety leadership plays a role in shaping safety climate and maintaining safety culture in the workplace. This research is important because cultivating a positive safety climate and culture can lead to reduced accidents in the workplace, higher employee morale, and overall organizational performance.